MENINJAU KESEHATAN MENTAL PELAJAR: PERAN REGULASI EMOSI DAN DUKUNGAN SOSIAL [EXAMINING MENTAL HEALTH AMONG STUDENTS: THE ROLE OF EMOTIONAL REGULATION AND SOCIAL SUPPORT] - Nisa', Syasya Khoirin (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to determine the mental health condition of students in terms of the role of emotional regulation and social support. This study used a quantitative approach with a sampling technique in the form of accidental sampling and involved 290 students in grades 7 and 8 at a MTsN 'Z' in Blitar Regency as participants. The results showed that 32% or a total of 91 students had a low level of mental health. The results of this study also found that emotional regulation was able to predict mental health by 13.3% (estimate = 0.637, p 0.001), social support was able to predict mental health by 25.4% (estimate = 0.756, p 0.001) and social support was able to be a partial mediator in the role of emotional regulation on mental health (estimate = 0.268, p 0.001). Furthermore, the significance value obtained for the indirect effect was less than 0.001 (p 0.05) which means significant, with a mediation percentage of 42.1%. The direct effect also obtained a significance value of 0.001, indicating significant, with a mediation percentage of 57.9%. The conclusion of this study is that social support can partially mediate the role of emotional regulation on the mental health of students.